(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the preparation and physicochemical properties of a new polyampholytic polycomplexone based on polyacrylonitrile are studied. In order to analyze the ionogenic groups of the synthesized polyampholytic polycomplexone, potentiometric titration was carried out and IR spectra were obtained. The sorption of Cu2+ ions by the obtained polycomplexone was studied and analyzed using the X-ray fluorescence method.